Can Market Integration Explain Informational Efficiency Of Malaysian Listed Firms? - Tai, Kui Guan (2013)
Market integration and market efficiency are two important concepts in finance. Although debates on these concepts are still ongoing among practitioners and academicians, but it is still very few of empirical studies to explore the effect of market integration on market efficiency. The objective of this thesis is to examine whether global information transmits fast into share price if a company is highly integrated with the world stock market. On the contrary, a segmented firm that has higher integration with local stock market is expected to have slow response to global news. This thesis is to investigate whether the above hypotheses are valid for listed firms in Malaysia, a fast emerging market that consist of a large pool of both integrated and segmented firms. The sample study consists of 265 stocks listed on the Main Market of Bursa Malaysia and the data are from January 1995 to December 2010. The degree of market integration is measured by the variance ratio approach proposed by Akdogan (1997) while the informational efficiency is captured by the price delay measure of Hou and Moskowitz (2005). The price delay measure is designed to gauge the speed of stock prices adjust to new market-wide information, given that in an efficient market with complete information and rational investors, stock prices should adjust immediately to the arrival of new information. Besides, the determinants of price delay measure have received strong empirical support and well grounded theoretically. Therefore, this thesis also controls for the effects of investibility, firm size, turnover and volatility in the panel regression.